KNOWING SLOWLY: UNFOLDING THE DEPTHS OF MEANING: with Harris Wiseman and Fraser Watts, "Spiritual Intelligence: Participating with Heart, Mind and Body"; Harris Wiseman, "Knowing Slowly: Unfolding the Depths of Meaning"; Harris Wiseman, "The Japanese Arts and Meditation‐in‐Action"; Harris Wiseman, "Meaning and Embodiment in Ritual Practice"; and Harris Wiseman, "Theoria to Theory (and Back Again): Integrating Masterman's Writings on Language and Religion." (Zygon: Journal of Religion & Science, 2022)
The article explores an aspect of spiritual intelligence characterized as a lifelong search for meaning. Slow knowing involves wrestling with perplexity. Periods of such tarrying gradually facilitate an unfolding of meaning. More than just the content of one's knowledge, it is the relationship, the how or manner of one's relationship with meaning that grounds the spiritual generativity of the seeking. Slow knowing is presented as an existential orientation, a lifelong process akin to ongoing conversion. Part 1 distinguishes such slow knowing from other senses of slow in current discourse (Kahneman's fast/slow thinking framework, and meditative concepts of slow mind). Part 2 explores slow knowing through the lenses of lectio divina and the use of metaphor in religious language. Slow knowing is characterized as having both individual and social dimensions. The article concludes with the concern that the conditions needed for slow knowing—and thus for spiritual intelligence—are undermined by the hasty pace of contemporary life.